Implementation of Offline Travel Agent Promotion Model to Increase Room Occupancy - Putu Wila Pradnya Paramita; I Putu Astawa; I Gusti Agung Bagus Mataram; I Putu Sudira (The Postgraduate School of Tourism Sahid Polytechnic, 2022)
ABSTRACT Purpose: The purpose of this research is to find out the implementation of a promotion model for offline travel agents at The Ritz-Carlton Bali, Indonesia, and to find out how is the influence of reservation through offline travel agents to increase room occupancy at the hotel. Research methods: The data analysis technique was carried out with qualitative analysis and quantitative analysis. Qualitative analysis is performed on primary data by interview and direct observation, to find out the promotional model carried out at hotel for offline travel agents in an effort to increase room occupancy at The Ritz-Carlton Bali. Quantitative analysis is performed on secondary data, such as classic assumption test, simple linear regression analysis, correlation analysis, t-test, and coefficient of determination by using SPSS version 25. Results and discussion: Nowadays the accommodation competition in tourism industries is very tight and The Ritz-Carlton Bali is trying to win the competition by implementing the offline travel agent promotion model in an effort to increase room occupancy rate. Implication: Based on the result of coefficient determination in this study, reservation through offline travel agent has significant influence to the room occupancy rate of 54,8% while 45,2% is influenced by other factors. Keywords: promotion, reservation, offline travel agent, room occupancy.